2022
DOI: 10.3390/electronics11040532
|View full text |Cite
|
Sign up to set email alerts
|

4H-SiC Schottky Barrier Diodes as Radiation Detectors: A Review

Abstract: In this review paper, an overview of the application of n-type 4H-SiC Schottky barrier diodes (SBDs) as radiation detectors is given. We have chosen 4H-SiC SBDs among other semiconductor devices such as PiN diodes or metal-oxide-semiconductor (MOS) structures, as significant progress has been achieved in radiation detection applications of SBDs in the last decade. Here, we present the recent advances at all key stages in the application of 4H-SiC SBDs as radiation detectors, namely: SBDs fabrication, electrica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Typical concentrations of Z 1/2 in the as-prepared material are 10 11 -10 13 cm −3 . The defect appears as a peak with a maximum at about 320 °K in the DLTS spectrum [9]. A broad peak in the DLTS spectrum at about 650 °K is the signature of the EH 6/7 deep level defect [9].…”
Section: Defects In Sicmentioning
confidence: 99%
See 4 more Smart Citations
“…Typical concentrations of Z 1/2 in the as-prepared material are 10 11 -10 13 cm −3 . The defect appears as a peak with a maximum at about 320 °K in the DLTS spectrum [9]. A broad peak in the DLTS spectrum at about 650 °K is the signature of the EH 6/7 deep level defect [9].…”
Section: Defects In Sicmentioning
confidence: 99%
“…Detailed reviews on the different ingredients of a SiC detector recipe can be found in Refs. [4,5,9,[20][21][22][23][24]. Although a detailed description of the fabrication techniques of a SiC detector is behind the scope of this paper, this Section summarizes the main aspects of the growth/deposition techniques and the properties of the above-mentioned building blocks.…”
Section: Sic Detector Fabricationmentioning
confidence: 99%
See 3 more Smart Citations